PENINGKATAN BERAT BADAN DAN LAMA PENGUNAAN METODE SUNTIK PROGESTIN PADA AKSEPTOR AKTIF - Khobibah Khobibah; Budi Astyandini; Mimi Ruspita (Midwifery Care Journal, 2020)
Progestin injection contraception is one of hormonal contraception. Approximately 56% choosen this contraception. Progesteron contraception contained side effects in long term use.  One of side effect is increasing body weight related of fat accumulation. Aim of this research is to find out the relationship between long term use with increasing of weight gain on acceptor. This research use analitical observasional with 35 sampling acceptor. The age of the acceptor was more than 30 years old. The age of the acceptor was more than 30 years old in Purwosari village, Patebon Kendal. This research use observasional checklist and use Pearson Correlation test. The result showed correlation between longterm use with increasing of bdoy weight gain that was p 0,338 with significancy value 0,048 0,05. In conclusion there was correlation long term use and increasing of body weight gain. There was intervention to reduce body weight gain and the measurement of lipid profil on acceptor.